BRIDGING DOCUMENTATION GAPS IN ELECTRONIC MEDICAL RECORDS: AN ANALYSIS OF INCOMPLETE MEDICAL ASSESSMENTS AND THEIR CONSEQUENCES FOR INA-CBGS REIMBUREMENT - Ika Setya Purwanti; Made Wahyu Aditya (PT. Jurnal Center Indonesia Publisher, 2025)
Electronic Medical Records (EMR) are designed to improve service quality, documentation accuracy, and administrative efficiency, including reimbursement through the Indonesian Case-Based Groups (INA-CBGs). However, incomplete medical assessments remain a challenge, potentially leading to service gaps and reduced hospital claims. This qualitative descriptive study was conducted at Dharma Yadnya General Hospital, Denpasar, which has fully implemented EMR since 2024. Data were obtained through in-depth interviews with five informants: two medical record officers, the head of the emergency nursing unit, the head of the inpatient nursing unit, and the head of the medical record department. Data analysis used the 3M framework: Man, Method, and Material. From the Man aspect, heavy workloads of doctors and the lack of administrative support staff often caused delays and incomplete documentation. From the Method aspect, although Standard Operating Procedures (SOPs) and system reminders existed, monitoring relied mainly on manual follow-ups via WhatsApp groups, limiting effectiveness. From the Material aspect, the EMR system was user-friendly and supported by weekly vendor maintenance, but occasional network disruptions and insufficient administrative staff still hampered real-time documentation. Incomplete medical assessments in EMR directly affect INA-CBGs claims, especially when comorbidities, complications, or procedures are not recorded, resulting in under-coding and reduced reimbursement. Strengthening human resources, enforcing SOPs, and improving system support are essential to ensure documentation completeness, service quality, and financial sustainability